Harmonization of Islamic Legal Institutions and Customary Law in Marriage Dispensation Cases at the Panyabungan Religious Court - Sebyar, Muhamad Hasan (Faculty of Sharia, IAIN Metro, 2023)
Harmonization between customary law and Islamic law (fiqh) has long occurred in our homeland. This study aims to illustrate the harmonization between Islamic legal institutions and customary institutions. This research is an empirical legal research, empirical legal research is research whose object of research is the practice of legal events or occurrences. The approach used in this study is a socio-legal approach, that used to analyze the social interactions between the Panyabungan Religious Court and customary institutions in implementing age dispensation. The results of this study show that this harmonization had run well between Islamic legal institutions and customary institutions. There is harmonization of existing norms or rules that apply in society. In substance making Islam more widespread in society and the state, from the understanding of classical jurisprudence to other legal products namely qadla, Islamic Law in substance continued to develop and acquire all regulations towards the rule of Islamic law as a whole. The similarity of certain functions within the customary law system, the Islamic legal system, and the national legal system according to the scope of their duties determines the extent to which harmonization occurs. The method of harmonization between Islamic law and customary law can be achieved in three ways, namely first; Harmonization of understanding, Second; Harmonization is carried out actively,Third; Passive harmonization.